2021
DOI: 10.3389/fonc.2021.634648
|View full text |Cite|
|
Sign up to set email alerts
|

Development, Validation, and Visualization of A Web-Based Nomogram for Predicting the Recurrence-Free Survival Rate of Patients With Desmoid Tumors

Abstract: BackgroundSurgery is an important treatment option for desmoid tumor (DT) patients, but how to decrease and predict the high recurrence rate remains a major challenge.MethodsDesmoid tumor patients diagnosed and treated at Tianjin Cancer Institute & Hospital were included, and a web-based nomogram was constructed by screening the recurrence-related risk factors using Cox regression analysis. External validation was conducted with data from the Fudan University Shanghai Cancer Center.ResultsA total of 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This tumor represents a rare, locally aggressive soft tissue neoplasm, which is recognized as semimalignant with high tendency for local recurrence 7,8 . The 3-year and 5-year recurrence-free survival rates of this neoplasm were 82.5 and 78%, while the 5-year survival rate is greater than 98% 9,10 . The patient did not undergo adjuvant chemotherapy or radiotherapy.…”
Section: Case Reportmentioning
confidence: 76%
“…This tumor represents a rare, locally aggressive soft tissue neoplasm, which is recognized as semimalignant with high tendency for local recurrence 7,8 . The 3-year and 5-year recurrence-free survival rates of this neoplasm were 82.5 and 78%, while the 5-year survival rate is greater than 98% 9,10 . The patient did not undergo adjuvant chemotherapy or radiotherapy.…”
Section: Case Reportmentioning
confidence: 76%
“…45 Postsurgical relapse rates were higher for extra-abdominal DTs than for abdominal DTs and among juvenile patients versus adult patients, 46 and nomograms that incorporated tumor size Cancer August 15, 2022 to predict postsurgical recurrence were subsequently developed. 27,49 A recent Danish study reported that rates of surgery as initial DT treatment fell from 75% between 2009 and 2014 to 32% between 2015 and 2018. 50 Several factors have combined to unseat surgery as the de facto first-line standard treatment for most patients with DT.…”
Section: Surgery and Radiotherapymentioning
confidence: 99%
“…Microscopically margin‐negative (R0) resections were not achieved in most surgeries, and there was no consensus on whether a positive margin resection correlated with the risk of recurrence 45 . Postsurgical relapse rates were higher for extra‐abdominal DTs than for abdominal DTs and among juvenile patients versus adult patients, 46 and nomograms that incorporated tumor size to predict postsurgical recurrence were subsequently developed 27,49 …”
Section: Local Control Strategiesmentioning
confidence: 99%